Selectionist Epistemology and Non-Adaptationist Epistemology: Outlook of Some Problems in Evolutionary Epistemology - Cadavid Ramírez, Lina Marcela (Estudios de Filosofía, 2016)
This paper presents some philosophical problems concerning evolutionist epistemology (selectionist epistemology) as an interdisciplinary discourse that seeks to explain the classical issues in the teory of knowledge. In order to develop these problems, it will be necessary to discuss some aspects that have been criticized with regard to the role that evolutionist epistemology has given to natural selection in the process of knowledge. These critiques arise from another theoretical perspective, the non-adaptationist epistemology, as understood by Franz Wuketits. From this discussion between selectionist epistemology and non-adaptationist epistemology, this paper reviews the Donald T. Campbell notion of downward causation and the importance that Wuketits gives to the interaction between organism and environment.